Science teachers' consideration: a phenomenographic study of learner-centred teaching analysis. Issue 3 (27th May 2021) - Lee, Wei Ching; Der-Thanq Chen, Victor; Wang, Li-Yi
ABSTRACT: Teachers' consideration may affect their intention to implement learner-centred pedagogy. Literature showed that aspects such as task goal, students' characteristics, teachers' ability, learning environment design, and school shape teacher considerations in teaching analysis. However, the interrelationship among these aspects remains largely underexplored. This study aims to explore science teachers' considerations when designing and implementing learner-centred teaching tasks and the interrelationship among them. Through phenomenographic analyses, the authors identified five categories of experiencing teaching analysis: (a) covering the curriculum contents; (b) preparing students for assessment; (c) accommodating students' characteristics; (d) designing appropriate learner-centred pedagogy; and (e) enhancing students' autonomy and social interaction. Findings suggest that teachers' considerations in the first three categories were limited to the classroom settings, while the last two categories show extension from classrooms to beyond school settings. The authors suggest school leaders and teacher educators leverage teachers' pragmatic reasoning to raise the holistic awareness and extend the horizon of teachers' consideration.